Challenges and opportunities of clinical pharmacy services in Ethiopia: A qualitative study from healthcare practitioners' perspective - Tegegn HG; Abdela OA; Mekuria AB; Bhagavathula AS; Ayele AA (Centro de Investigaciones y Publicaciones Farmaceuticas, 2018)
Background: Currently, clinical pharmacists have in-depth therapeutic knowledge and scientific skills to act as drug therapy experts in healthcare settings. Objective: The aim of this study was to assess the opportunities and challenges of clinical pharmacy services from the health practitioners' perspective in University of Gondar (UOG) hospital Ethiopia. Methods: A qualitative study was performed using face-to-face in-depth interviews with health practitioners who were directly involved in clinical pharmacy services (clinical pharmacists, physicians, and nurses) in UOG hospital. Results: A total of 15 health professionals from various specialties were interviewed to express their views towards clinical pharmacists' competencies and identified challenges and opportunities regarding their clinical services. Based on interviewees report, the opportunities for clinical pharmacists includes acceptance of their clinical services among health specialties, new government policy and high patient load in hospital. However, inadequacy of service promotions, lack of continuity of clinical pharmacy services in wards, poor drug information services, lack of commitment, lack of confidence among clinical pharmacists, conflict of interest due to unclear scope of practice, and absence of cooperation with health workers were some of the challenges identified by the interviewees. Conclusion: We identified health professionals working in UOG hospital are receptive towards clinical pharmacy services, but identified some of the potential challenges that needed to be focused to strengthen and promote clinical pharmacy services. Further, the opportunities at hand also need to be utilized astutely to boost the services.